The 13-story treehouse - Griffiths, Andy, 1961-; Denton, Terry (New York : Feiwel and Friends, 2013)
Andy and Terry are trying hard to write their next book but they are constantly distracted by the many animals and special rooms in their thirteen story treehouse.
Pub Weekly, February 2013.
5.0
3-6
560L
Keywords: Tree houses -- Juvenile fiction; Books and reading -- Juvenile fiction; Authors -- Juvenile fiction; Illustrators -- Juvenile fiction; Tree houses -- Fiction; Books and reading -- Fiction; Authors -- Fiction; Illustrators -- Fiction; Tree houses -- Fiction; Books and reading -- Fiction; Authors -- Fiction; Illustrators -- Fiction; Tree houses -- Fiction; Authors -- Fiction; Writing -- Fiction; Humorous stories